The Parasocial Dimension of Scripture - Dault, David (Postscripts: The Journal of Sacred Texts, Cultural Histories, and Contemporary Contexts, 2025)
This article draws on the work of Morgan Ames to consider scripture as a form of charismatic technology. Building on that premise, the article suggests an as-yet unexplored point of connection between the work of James Watts and Kristina Myrvold regarding the material analysis of scripture. Drawing on Watts’s essay, “The Three Dimensions of Scripture,” this article then offers a complementary fourth dimension, the parasocial dimension, which recognizes the charismatic power of scripture to function as an object that makes demands of devotees. The article concludes with the call to religious scholars to take a deflationary approach to this parasocial dimension, turning away from the charismatic agency of the object and returning agency and responsibility to humanity, where it ultimately belongs.